Impactos da integração do Brasil com a União Europeia e o BRICS no Brasil através de um modelo de equilíbrio geral - Schunke, Jaqueline Castegnaro (Universidade do Vale do Rio dos Sinos, 2015)
This study analyses the bilateral trade between Brazil and the European Union and Brazil and BRICS in the period 1991-2001, examining the trade opportunities per sector according to its technological intensity, with special focus at tobacco market. It employs a computable general equilibrium model from the Global Trade Analysis Project (GTAP), with an initial equilibrium in 2001using 57 sectors and those major participants in tobacco trade, eliminating the import tariffs among Brazil and the European Union and the BRICS countries. The results show that both scenarios have similar outcomes, even more intensively for the second simulation. Production and exports of primary products rose in Brazil, resulting in increases in welfare. On the other hand, technology intensive products have decreasen its production and exports, deepen the recent process of primarization of Brazilian exports. For tobacco, there is also an increase of its exports, especially to BRICS. The results also show an increase in the process of reprimarization of Brazilian exports, reducing the production of those sectors with higher technological intensity in both scenarios.
Keywords: Integração econômica; União Europeia; BRICS; GTAP; Tabaco; Economic integration; European Union; Tobacco; ACCNPQ::Ciências Sociais Aplicadas::Economia